Additive manufacturing of rectangular waveguide devices for teaching microwave laboratory - Márquez-Segura, Enrique (My University, 2019)
In this paper the outline of using of low-cost additive manufacturing FDM/FFF technology to build waveguide devices is presented. The focus is set in a full design from specifications to final measurements in a microwave teaching laboratory. Final results obtained asses that this experience is an extraordinary opportunity for students to get involved in waveguide technology. In addition, the use of 3D design software enriches the curricula of electronic engineering students.
Keywords: Electromagnetismo; Additive manufacturing; Trl calibratin; Microwave laboratory